Corrosion Monitoring in Atmospheric Conditions: A Review - Kateryna Popova; Tomáš Prošek (Metals, 2022)
A variety of techniques are available for monitoring metal corrosion in electrolytes. However, only some of them can be applied in the atmosphere, in which case a thin discontinuous electrolyte film forms on a surface. In this review, we describe, evaluate and compare both traditional and state-of-the-art real-time corrosion monitoring techniques to identify those suitable for atmospheric conditions. For atmospheric corrosion monitoring (ACM), electrochemical impedance spectroscopy (EIS), electrochemical noise (EN), electrical resistance (ER) probes, quartz crystal microbalance (QCM), radio-frequency identification sensors (RFID), fibre optic corrosion sensors (FOCS) and respirometry, the underlying principles, characteristics and application examples are described, and their advantages and drawbacks outlined. Finally, the techniques are compared in terms of their sensitivity, ease of setup, data processing, ability to identify underlying corrosion mechanisms and applicability in different fields of atmospheric corrosion protection and research.